2017
DOI: 10.1038/bjc.2017.316
|View full text |Cite
|
Sign up to set email alerts
|

Circulating cytokines and small molecules follow distinct expression patterns in acute myeloid leukaemia

Abstract: Background:Although aberrant expression of cytokines and small molecules (analytes) is well documented in acute myeloid leukaemia (AML), their co-expression patterns are not yet identified. In addition, plasma baselines for some analytes that are biomarkers for other cancers have not been previously reported in AML.Methods:We used multiplex array technology to simultaneously detect and quantify 32 plasma analyte (22 reported analytes and 10 novel analytes) levels in 38 patients.Results:In our study, 16 analyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
(24 reference statements)
0
11
0
Order By: Relevance
“…These analyses focused on cytokines, as previous studies had demonstrated that aberrant cytokine expression is nearly universal in AML/MDS and that some cytokines exhibit potential prognostic and/or predictive value or are implicated in AML/MDS pathobiology (including IL6, IL8, IL10, VEGF, and TNFa; refs. [22][23][24][25][26][27]. Moreover, Hh pathway signaling has been shown to modulate the expression of proinflammatory molecules such as TNFa, IL1b, and IL6 (28).…”
Section: Molecular Profiling and Pharmacodynamic Analysesmentioning
confidence: 99%
“…These analyses focused on cytokines, as previous studies had demonstrated that aberrant cytokine expression is nearly universal in AML/MDS and that some cytokines exhibit potential prognostic and/or predictive value or are implicated in AML/MDS pathobiology (including IL6, IL8, IL10, VEGF, and TNFa; refs. [22][23][24][25][26][27]. Moreover, Hh pathway signaling has been shown to modulate the expression of proinflammatory molecules such as TNFa, IL1b, and IL6 (28).…”
Section: Molecular Profiling and Pharmacodynamic Analysesmentioning
confidence: 99%
“…Studies evaluating pro-and antiinflammatory cytokine and growth factor levels in serum revealed that GM-CSF, IL-1b, IL-3, IL-4, IL-5, IL-6, IL-8, IL-10, IL-12p70, IL-27, IL-35, osteopontin and stem cell factor (SCF) are upregulated in all or in distinct AML patient groups compared to age-matched controls (39)(40)(41)(42)(43). In contrast to most cytokines, TRAIL and TGF-b levels are decreased in the serum of AML patients (39,43,44). To gain insights into the specific functions of individual cytokines and growth factors in AML, numerous studies have characterized the effects of recombinant cytokines and HGFs on proliferation and colony formation of primary AML cells and cell lines in vitro, thereby establishing ex vivo AML cell culture conditions (see Table 1).…”
Section: Role Of Cytokines In Amlmentioning
confidence: 99%
“…Osteopontin Elevated PB and BM levels(44, 82, 83) Matrix glycoprotein with proinflammatory cytokine properties Supports AML cell self-renewal, proliferation and survival (84)…”
mentioning
confidence: 99%
“…AML is a heterogeneous group of diseases characterized by myeloid progenitor cells with abnormal proliferation and differentiation (96). Similar to CLL, the serum levels of MIF are increased in AML compared with healthy bodies (97). This indicates that the presence of MIF in the microenvironment may serve an important role in the pathogenesis of AML.…”
Section: Functions Of Mif In Leukemiamentioning
confidence: 99%